The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0100-29452006000100031
|View full text |Cite
|
Sign up to set email alerts
|

Doses de nitrogênio e potássio em fertirrigação em maracujazeiro-amarelo consorciado com coqueiro-anão verde, na região Norte Fluminense

Abstract: RESUMO -Com o objetivo de avaliar os efeitos de doses de nitrogênio (N) e potássio (K) na água de irrigação, sobre a produtividade e os teores foliares de nutrientes minerais em maracujazeiro-amarelo consorciado com coqueiro-anão verde no Norte Fluminense, foi instalado um experimento em delineamento inteiramente casualizado, com 2 tratamentos (2 doses de adubação, em fertirrigação: 1) N=161 e K=215 kg ha -1 ano -1 , e 2) N=322 e K=430 kg ha -1 ano -1 ) e 12 repetições, em um solo classificado como Neossolo Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
1
0
2
Order By: Relevance
“…The present study confirms the results obtained by Rosa et al (2006), who evaluated the effects of two N and K doses via fertigation on yellow passion fruit cultivated in consortium with dwarf coconut in northern of Rio de Janeiro state and by Venâncio et al (2013), who evaluated the effects of increasing nitrogen doses on yellow passion fruit FB-200 cultivar in the first year of cultivation in Aquidauana-MS. The same authors attributed these results to high soil fertility and use of irrigation which increase nutrients efficiency utilization by plants.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The present study confirms the results obtained by Rosa et al (2006), who evaluated the effects of two N and K doses via fertigation on yellow passion fruit cultivated in consortium with dwarf coconut in northern of Rio de Janeiro state and by Venâncio et al (2013), who evaluated the effects of increasing nitrogen doses on yellow passion fruit FB-200 cultivar in the first year of cultivation in Aquidauana-MS. The same authors attributed these results to high soil fertility and use of irrigation which increase nutrients efficiency utilization by plants.…”
Section: Resultssupporting
confidence: 91%
“…BRS Gigante Amarelo, BRS Ouro Vermelho and BRS Sol do Cerrado cultivars average fruit weight was considered adequate in comparison to results obtained by Meletti (2011), who found for the same cultivars average fruit weight ranging from 120 to 350 g. Rosa et al (2006) obtained average yellow passion fruit weight higher than 160 g in both N and K doses. However, IAC 275 cultivar average fruit weight and average yield obtained in this study were below 180 g and 48 t ha -1 , respectively, indicated for this cultivar (MELETTI, 2001 (Vale et al, 2013).…”
Section: Resultsmentioning
confidence: 64%
“…Os mesmos autores ainda afirmam que não há um consenso a respeito da dose ótima para se obter um máximo rendimento da cultura do girassol, aparentemente, a resposta do girassol a diferentes doses de N depende da cultivar e das condições ambientais. Irriga, Botucatu, v. 20, n. 4, p. 667-679, outubro -dezembro, 2015 Nos últimos anos, a forma tradicional de adubação vem sendo substituída pela fertirrigação que tem como vantagem uma maior eficiência e economia dos fertilizantes (ROSA et al, 2006). Em sistemas mais avançados de exploração de culturas, o emprego da fertirrigação está se tornando rotina (MIRANDA et al, 2008).…”
Section: Introductionunclassified
“…Neste sentido, a utilização mais eficiente de nutrientes permite que a ferti-irrigação seja uma alternativa viável para suprir a carência nutricional do coqueiro, promovendo uma maior produção. Rosa et al (2006) observaram que o uso da ferti-irrigação aumentou a produtividade e, como consequência, a melhoria da qualidade dos frutos, sendo uma ótima técnica para solos que têm problemas com fertilidade, como os solos que são cultivados pela maioria dos produtores de coqueiros na região Nordeste. Por isto, pesquisas nestas áreas devem ser estimuladas, sobretudo, para culturas adaptadas ao clima nordestino, sendo diferencial para os produtores de coco desta região.…”
Section: Introductionunclassified